David Robinson - Robinson, David; Nang ChanYeema (United States of America Zondervan Publishing House, 1996)
Focuses on the personal life and Christian upbringing of the basketball star who played for the Naval Academy and the 1988 Olympic team before becoming center for the San Antonio Spurs.
Keywords: Adult Nonfiction